Design and characterization of 3D AuxHex lattice structures. (1st September 2020) - Guo, Meng-Fu; Yang, Hang; Ma, Li
Highlights: Novel 3D AuxHex lattice structures are proposed with zero Poisson's ratio and fabricated via 3D printing. The 3D AuxHex lattice has better energy absorption compared with re-entrant structure with the same relative density. Functionally graded AuxHex lattices are used to control the stress-strain curves and improve energy absorption performances. Hybrid stable AuxHex lattices are developed with enhanced plateau stress and energy absorption efficiency. Abstract: In this paper, a novel three dimensional (3D) AuxHex lattice structure consisting of auxetic re-entrant and hexagonal components is proposed. Theoretical models of elastic constants and quasi-static plateau stress are established which indicate that the AuxHex lattice structures have zero Poisson's ratio and better energy absorption capacity than traditional auxetic re-entrant cellular structures. Numerical simulation is also used to study the mechanical properties of 3D AuxHex lattice structures, which presents good agreements with theoretical models. The experimental specimens are fabricated via 3D printing technique and the compression tests are also carried out to validate the accuracy of theoretical models and numerical simulations. To overcome the problem of unstable quasi-static crushing of 3D AuxHex structures with thin struts (low relative density), the hybrid stable AuxHex lattice (HSAL) structure is designed by inserting auxiliary structure to AuxHex lattice to make the AuxHex structures more stable and obtain higher energy absorption efficiency. The influence of material gradient index is investigated numerically, which shows the positive and negative gradients have different effects on the energy absorption behavior under various loading conditions. Graphical abstract: Image, graphical abstract